On-Chip Electrochemical Sensor Based on 3D Graphene Assembly Decorated Ultrafine RuCu Alloy Nanocatalyst for In Situ Detection of NO in Living Cells - Haibo Liu; Kaiyuan Yao; Min Hu; Shanting Li; Shengxiong Yang; Anshun Zhao (Nanomaterials)
In this work, we developed 3D ionic liquid (IL) functionalized graphene assemblies (GAs) decorated by ultrafine RuCu alloy nanoparticles (RuCu-ANPs) via a one-step synthesis process, and integrated it into a microfluidic sensor chip for in situ electrochemical detection of NO released from living cells. Our findings have demonstrated that RuCu-ANPs on 3D IL-GA exhibit high density, uniform distribution, lattice-shaped arrangement of atoms, and extremely ultrafine size, and possess high electrocatalytic activity to NO oxidation on the electrode. Meanwhile, the 3D IL-GA with hierarchical porous structures can facilitate the efficient electron/mass transfer at the electrode/electrolyte interface and the cell culture. Moreover, the graft of IL molecules on GA endows it with high hydrophilicity for facile and well-controllable printing on the electrode. Consequently, the resultant electrochemical microfluidic sensor demonstrated excellent sensing performances including fast response time, high sensitivity, good anti-interference ability, high reproducibility, long-term stability, as well as good biocompatibility, which can be used as an on-chip sensing system for cell culture and real-time in situ electrochemical detection of NO released from living cells with accurate and stable characteristics in physiological conditions.